Philosophy in time(s) of terror - Reinhart, David (The journal for cultural and religious theory, 2004)
A review of Philosophy in a Time of Terror: Dialogues with Jürgen Habermas and Jacques Derrida, edited by Giovanna Borradori. Chicago: The University of Chicago Press, 2003. 200 pp. $25.00 cloth. ISBN: 0-22-606664-9.